Kinetics of bipedal locomotion during load carrying in capuchin monkeys. Issue 85 (August 2015) - Hanna, Jandy B.; Schmitt, Daniel; Wright, Kristin; Eshchar, Yonat; Visalberghi, Elisabetta; Fragaszy, Dorothy
Abstract: Facultative bipedalism during load transport in nonhuman primates has been argued to be an important behavior potentially leading to the evolution of obligate, extended limb bipedalism. Understanding the biomechanics of such behavior may lead to insights about associated morphology, which may translate to interpretation of features in the fossil record. Some populations of bearded capuchin monkeys ( Sapajus libidinosus ) spontaneously carry heavy loads bipedally during foraging activities. This study provides the first data on all three components of ground reaction force for spontaneous bipedalism during load carriage in a nonhuman primate. Five individual S. libidinosus (mean body mass = 2.4 kg ± 0.96) were videorecorded during bipedalism while carrying a stone (0.93 kg) under natural conditions. A force plate was embedded in the path of the monkeys. Spatiotemporal and force data for all three components of the ground reaction force were recorded for 28 steps. Capuchins exhibited a mean vertical peak force per total weight (Vpk) for the hindlimb of 1.19 (sd = 0.13), consistent with those of unloaded capuchins in the laboratory and for other bipedal primates, including humans. Vertical force records suggest that capuchins, along with most nonhuman primates, maintain a relatively compliant leg during both unloaded and loaded locomotion. Like all other primates, loaded capuchins maintained laterally (outward) directed medio-lateral forces, presumably to stabilize side-to-side movements of the center of mass. Medio-lateral forces suggest that at near-running speeds dynamic stability diminishes the need to generate high lateral forces. Vertical force traces exhibited a measurable impact spike at foot contact in 85% of the steps recorded. An impact spike is common in human walking and running but has not been reported in other bipedal primates. This spike in humans is thought to lead to bone and cartilage damage. The earliest biped may have experienced similar impact spikes during bipedal locomotion, requiring compensatory behaviors or anatomical features.